IBM RANCANG BANGUN MESIN PENGERING DAN SETRIKA UAP UNTUK MENINGKATKAN PRODUKTIFITAS KELOMPOK USAHA LAUNDRY - Agus Efendi (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2014)
The objective of IbM program is the application prototype of dryer clothes based on gas resources andsteam iron as well as low energy, so hopefully with these tools can streamline the production time, minimizecomplaints due to human error, it is easy to use (ability), service quality is guaranteed (high quality), and canimprove the modernization of the laundry business community in general. The method applied to the IbMprogram is uses the review follow-method approach consisting of several methods for achieving the goal ofincreasing productivity, effectiveness and quality of production through the application of the prototype. Stagesmethods applied include: design stage, executing test machinery and equipment, the preparation of instructionson the equipment operation, counseling stage, mentoring stage, as well as monitoring and evaluation stage ofproducts with renewable equipment to determine the extent to which the design can be useful tools to effectivelyand efficient.IbM superficial is application of appropriate technology in the form of drying machine product “gasdryer convection” and “steam iron”, to solve the problems that complaints by user and business partners of“Auralia Laundry” and “Dolphin Laundry” as laundry business manager.The results of IbMprogram then willbe published in the form of scientific papers.Implementation of IbM program output is the application of engineering systems of GasDryerConvectionand steam irons in the “laundry” business in the field impacted can increase productivity andeffectiveness in speeding up the production pace, quantity and quality can be achieved according to customerrequirements, production capacity can be increased and rapidly as indicated by high productivity, effective andefficient so that it can increase the needs order. With fulfillment of customer needs as a customer, it can foster asense of trust and the popularity of the work done more competitive and efficient. In closing, looking forward tomore good by continuing to improve the productivity, effectiveness and adequate quality must be supported bythe government, private sector and universities . As a follow-up to the next plan will be improving productdesign to accommodate input and criticism from SMEs partners to output product.